Cuidado durante a internação do paciente com HIV/AIDS e seus familiares, e o impacto nos níveis de ansiedade e depressão - Quintanilha, Analice Cristhian Flavio (2022)
This research aimed to verify the perception of the person living with HIV/Aids (PLWHA) and family members of the person living with HIV/Aids (FPLHA) in relation to the care offered during hospitalization, considering the anxiety and depression index of these patients. People. OBJECTIVES: To characterize demographically PLWHA, FPLHA and health team professionals; to verify the perception of PLWHA, FPLHA and health team professionals about the care provided; identify the level of anxiety and depression of PLWHA and PLWHA; summarize the literature in relation to scientific evidence. METHODOLOGY: 02 scientific articles were published: Article 01, a narrative review, aimed to discuss issues related to the presence of the family in the treatment of PLWHA; the second a cross-sectional, quantitative article, which presented the socioeconomic profile, and the answers to the questionnaires: Hospital Anxiety and Depression Scale (HADS) and Perception of Care Centered in Adults and their Family (PCCPAF – Brazilian version), applied to PLWHA, FPHA and healthcare professionals. Article 03 was submitted and it was an integrative review, through which 43 articles were analyzed regarding the proposed theme. RESULTS: In article 01, the benefits of inserting FPLHA in the care of PLWHA were verified, and a model of care centered on the patient and family (CCPF) that uses this strategy was presented; the second article showed discrepancies in the responses of PLWHA and FPLHA in relation to the perception of being welcome during hospitalization and feeling included in the care; it was evidenced in some statements by PLWHA, FPLHA and professionals that there is a need to improve communication; it was found that all FPVHA and PLHA had varying levels of anxiety and depression; article 03 summarized the scientific productions about PLWHA, FPLHA and health professionals, in relation to the perception of care during hospitalization. CONCLUSION: With this study, it is concluded that: there is a communication failure on the part of professionals, who use technical vocabulary, causing PLWHA and FPLHA not to understand the information; that the professional’s self-perception is distorted and leads him not to see the damage caused by his attitudes, beliefs and values, making the vision of PLWHA and FPLWHA on the quality of care offered discrepant; that despite the PLWHA and the FPLHA not feeling perceived and not having their decisions validated, both did not verbalize their perceptions to the professionals, due to their lack of empowerment in relation to their treatment; during the period of hospitalization, PLWHA and FPLHA are exposed to a reality for which they were not prepared, at any stage of their lives, leading them to a variable degree of anxiety and depression, in short, the need for the development of new studies on the inclusion of the family in the hospital environment, focusing on the understanding of ways to incorporate the CCPF principles to issues related to patient safety and the perception of PLWHA, FPLHA and health professionals regarding the care provided. Keywords: Patient-centered care; Family; Depression; Patient care team; Aids.